Sistema chronometraža i informacionnogo obespecenija v velosipednom sporte (analiticeskoe obozrenie) - Rostovtsev, V. L.; Dogov, A. A.; Alyakritskiy, V. L.; Barmin, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The article attempts to provide an analytical review of existing developments in timing and information supply systems for masssports competitions currently used in Russia and abroad. Basic designs of timing systems, their advantages and disadvantages were determined on the basis of a patent and literature search. The most effective technologies for recording the passing time of stages and the entire distance were determined. The absence of single universal equipment and a comprehensive information supply system was revealed, which allows registering participants in mass sports competitions, creating protocols of the last competitions in accordance with the requirements of the sport's rules, maintaining ratings of participants in various sections, creating databases and giving information to all participants in the system. Based on the studies, recommendations on the equipment configuration and technologies for recording the passing time of the distances, directions of a unified comprehensive information supply system for year-round support of mass sports competitions in cyclic sports are given.